Lymphocutaneous Sporotrichosis Refractory to First-Line Treatment - Belda, Walter; Domingues Passero, Luiz Felipe [UNESP]; Stradioto Casolato, Ana Thereza (Hindawi, 2021)
Sporotrichosis is a fungal infection endemic in Latin America and has been attributed to the thermodimorphic fungus of the genus Sporothrix. Transmission to humans occurs during a traumatic injury with soil or organic material; additionally, lesions caused by infected cats play an important role in the epidemiology of the disease. The classic treatment of sporotrichosis is performed with itraconazole or potassium iodide; second-line medications, such as amphotericin B and terbinafine, can alternatively be used in cases of first-line drug failure. In the present study, a patient with lymphocutaneous sporotrichosis in the right upper limb exhibited intolerance to itraconazole and potassium iodide, additionally during the period of use; these drugs did not control skin lesions. In this patient, amphotericin B deoxycholate and its liposomal version were used in this patient; and complete recovery of the lesions was observed.